Making something out of Nada: An analysis of Yago and Jaén’s adaptation of Carmen Laforet’s novel as performed by the Centro Dramático Nacional. - Treadaway, Tallulah (Pygmalion. Revista de teatro general y comparado, 2025)
Adaptation is a dynamic process and useful tool in the study of culture. Carmen Laforet’s novel, Nada, first published in 1944 and winner of the first Premio Nadal in Spain was adapted for the stage under the direction of Beatriz Jaén at the Centro Dramático Nacional. This study explores what stands to be lost and gained when transforming a prose, with a specific focus on how theatrical techniques such as staging, lighting and characterisation transform elements of prose into features of a live stage performance. It also considers the differing social, political, and cultural contexts and the implications of adaptingNada for the modern Spanish stage. The writing of Linda Hutcheon inA Theory of Adaptation and Joyce Carol Oates in A Novelist Finds the Bare Bones of a Play provide a thorough foundation for this article with Patrice Pavis’s performance questionnaire similarly guiding the critical analysis..